Topographic Mapping of Road Network and Damage in Langsa Lama District using Geographic Information System (GIS) - Yulianto, Syukrizal; Nova Purnama Lisa; Wan Alamsyah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Roads are land transportation infrastructure and are a very vital transportation route. One of the functions of roads is as a driving factor in the development process and equitable development of an area, apart from that, roads also play an important role in the transportation process. Langsa Lama District is one of the fastest growing districts in Langsa City. This research aims to model the topographic mapping of the road network and road damage in Langsa Lama District using GIS and determine the damaged road network in Langsa Lama District. This research method is in the form of analyzing routes where there is road damage using a Geographic Information System which is divided into main stages, namely database development and data analysis starting from data collection and supporting maps. The final results of this research obtained a topographic map of the road network and road damage in Langsa Lama District, Langsa City.